Humanism Learning Theory: Implementation of the Independent Learning Curriculum in Primary Education / Madrasah Ibtidaiyah - Hamid, Widada; Imammudin, Aqil (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
In the context of modern education, the implementation of a curriculum that meets the individual needs of students is becoming increasingly crucial. At MI Plus Darussaadah Lirboyo, there is a need to explore the application of the Merdeka Belajar (Freedom to Learn) Curriculum based on Humanistic Learning Theory to address limitations in rigid and standardized teaching approaches. This study aims to evaluate the effectiveness of implementing the Merdeka Belajar Curriculum, which emphasizes humanistic principles in enhancing the quality of learning at MI Plus Darussaadah Lirboyo. The research employs a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews with teachers and students, and document analysis. The results indicate that the implementation of the Merdeka Belajar Curriculum based on humanism at MI Plus Darussaadah Lirboyo has successfully increased student motivation, strengthened teacher-student relationships, and supported the holistic development of students across cognitive, affective, and psychomotor domains. The implication of this research is that implementing a more flexible and student-centered curriculum can serve as an effective model for improving the quality of education in other educational institutions. Thus, the humanistic approach in education can make a significant contribution to achieving more inclusive and holistic educational goals.